Use of serum immunoglobulins G and A for detection of Helicobacter pylori infection in dyspeptic patients by enzyme immunosorbent assay - Babay Hannan (The Saudi Journal of Gastroenterology, 2000)
Since the discovery of Helicobacter pylori (H. pylori), several invasive and non invasive tests have become available. The aim of this study was to test the performance of immunoglobulins IgG and IgA by using an enzyme linked immunosorbent assay (ELISA) test (In vitro diagnostika GmbH, Germany) for the diagnosis of H. pylori among dyspeptic patients. Blood samples from 152 dyspeptic patients and 51 asymptomatic controls were analyzed in a case control study. IgG and IgA were positive in 33.5% and 41.1% respectively compared to 13.8% for both IgG and IgA in controls (P=0.002). We support the future use of serology as a non invasive, and rapid test for the diagnosis of H. pylori infection among dyspeptic patients in areas with low prevalence. Endoscopy remains the method of choice for elderly dyspeptic patients and for those with possible gastric or duodenal pathology.